1977
DOI: 10.1128/iai.16.3.923-927.1977
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and maintenance of acquired resistance in mice to Listeria monocytogenes

Abstract: In the mouse system, acquired resistance to Listeria monocytogenes can only be demonstrated after immunization with viable microorganisms. A successful state of immunity cannot be elicited with formalin-killed organisms or bacterial cell-derived products. Viable, serologically cross-reactive organisms (not mouse pathogenic) do not induce a state of immunity as measured by acquired resistance. The duration of immunity, once established, is dose independent, and the absolute interval of its existence is not exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1978
1978
2006
2006

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…It could be shown by the passive transfer of spleen cells that the mechanism of protective immunity is basically identical to the mode of action first described by Miki and Mackaness (12). Protective immunity, however, is rather short lived after primary infection with L. innocua, a finding that has been described by Kearns and Hinrichs (7) for infection with L. monocytogenes serotype 1/2b. The dose dependency of protective immunity after primary infection with L. innocua furthermore suggests that immunity can be acquired only when the animal host contains great numbers of microorganisms.…”
Section: Resultssupporting
confidence: 55%
“…It could be shown by the passive transfer of spleen cells that the mechanism of protective immunity is basically identical to the mode of action first described by Miki and Mackaness (12). Protective immunity, however, is rather short lived after primary infection with L. innocua, a finding that has been described by Kearns and Hinrichs (7) for infection with L. monocytogenes serotype 1/2b. The dose dependency of protective immunity after primary infection with L. innocua furthermore suggests that immunity can be acquired only when the animal host contains great numbers of microorganisms.…”
Section: Resultssupporting
confidence: 55%
“…Generation of acquired cellular resistance (ACR) to listerias characteristically requires immunization by sublethal inoculation of viable, virulent L. monocytogenes (7,10). However, Wirsing von Koenig et al (23) reported that extremely large doses of avirulent Listeria strains can stimulate host resistance to challenge from a virulent Listeria strain.…”
Section: Discussionmentioning
confidence: 99%
“…These virulent Listeria strains are able to replicate within professional phagocytes, as demonstrated during in vitro and in vivo studies (10,13). In contrast, exposure to either apathogenic Listeria strains or nonviable virulent L. monocytogenes fails to promote a protective immune response (1,3,6,7,12,22,23) unless associated with an adjuvant (19)(20)(21). Furthermore, antigen preparations derived from listerias fail to induce acquired resistance as well.…”
mentioning
confidence: 99%
“…The initial arguments which proposed that these two phenomena are direct manifestations of the same cell population were based on observations which showed an apparent inseparability of ACR and DTH during the immune response (17)(18)(19). This association is highlighted by the need for an active infection to induce both ACR and DTH, unless special immunizing techniques are applied (4, 14,21,29,[31][32][33]. Also, the kinetics of development and longevity of these responses are similar (17,24,26).…”
mentioning
confidence: 99%